2016
DOI: 10.1007/s10461-016-1419-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Adherence to Antiretroviral Therapy in a Rural Paediatric Cohort in KwaZulu-Natal, South Africa

Abstract: Achieving optimal adherence to ARV’s in a rural paediatric population is challenging. Monitoring adherence by frequent viral load assay is not always feasible or sustainable in rural communities. A relatively cheaper, reliable, valid and sustainable measure of adherence for children is required for routine management. This study retrospectively assessed adherence outcomes using monthly pill count and viral load data, including reasons reported for non-adherence, in a paediatric cohort in rural KwaZulu-Natal, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Objective measures consist of pharmacy refill pill count, electronic dose monitoring, drug detection in biologic samples and plasma HIV Viral load (VL); they are generally costly and sometimes less accepted by the patients [ 9 ]. Due to these advantages and disadvantages, a combination of multiple techniques has been suggested for better adherence assessment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Objective measures consist of pharmacy refill pill count, electronic dose monitoring, drug detection in biologic samples and plasma HIV Viral load (VL); they are generally costly and sometimes less accepted by the patients [ 9 ]. Due to these advantages and disadvantages, a combination of multiple techniques has been suggested for better adherence assessment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…ART reduces plasma viremia, increases the CD4 cell count, and ultimately improves the health of children living with HIV. Despite the benefits and availability of ART, medication adherence remains suboptimal among children living with HIV due to multiple barriers, notably reliance on caregivers and guardians to regularly administer medication [6][7][8]. In addition, ART may be associated with toxicities and adverse side effects that include anaemia [9], metabolic abnormalities [10][11][12], and reduced growth [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the increased pill burden, TB drugs interaction with protease inhibitors, while active TB can cause biologic effects of immune activation resulting in HIV viremia (27). ART adherence contributes to achievement of viral suppression thus EAC is recommended for PLHIV who have non-adherence issues or have detectable VL (11) (20) (28). Our findings showed about (44%) children had received EAC and were more likely to be non-suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported correlates of viral non-suppression among CYALHIV include being male, having had tuberculosis (TB), HIV status disclosure at an older age, experiencing ART adverse drug events, all of which have been associated with ART non-adherence (4)(9)(10). Some caregiver characteristics associated with viral non-suppression include one who isn’t the mother, caregiver substance abuse, poor socio economic status, inadequate social support (11) (12)(17). However, previous studies using routine programmatic data have been reported out of high HIV prevalence settings.…”
Section: Introductionmentioning
confidence: 99%